Political debates on American TV - Lazukova, Olena (Київський національний університет імені Тараса Шевченка, 2025)
This study examines the role of televised political debates in the United States as a key component of contemporary political discourse and their influence on the democratic process. The research focuses on the impact of such debates on voter education, candidate image construction, and the interaction between media and politics. Particular attention is paid to the ways in which media framing, presentation styles, and multimodal elements—including verbal and non-verbal communication—shape public perception and voter decision-making. The study employs a set of methodological approaches, including discourse analysis, Critical Discourse Analysis, and multimodal analysis, alongside general scientific methods such as induction, observation, modeling, and formalization. It investigates the historical evolution of televised debates, analyzes rhetorical and communicative strategies used by candidates, and explores the role of emerging media technologies, such as social media and real-time fact-checking, in amplifying or transforming debate messages. The scientific novelty of the research lies in its integrated approach to examining televised debates within the context of modern digital media ecosystems. It highlights how technological advancements reshape political communication and influence audience cognition. The practical significance of the study consists in its potential to improve debate formats and media practices, thereby contributing to a more informed electorate and enhancing democratic engagement. The findings of this research contribute to a deeper understanding of the relationship between media and democracy, emphasizing the growing importance of media literacy in the digital age.
Keywords: political discourse; political debates